2021
DOI: 10.1021/acs.energyfuels.1c01448
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Isotope Fractionation during Shale Gas Transport through Organic and Inorganic Nanopores from Molecular Simulations

Abstract: Carbon isotope fractionation is a promising method to predict gas-in-place content and evaluate the shale gas production stage. In this study, molecular simulations are conducted to investigate fractionation characteristics of 12CH4 and 13CH4 in high-Kn (Knudsen number) flows (Kn > 0.1) within organic and inorganic pores under shale reservoir conditions (353 K, 5–25 MPa). The results show that isotope fractionation is more obvious (i.e., the difference in transport capacities between 12CH4 and 13CH4 is larger)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…In an actual PEMFC system, a pressure difference is generated due to the different stoichiometric ratios of hydrogen and air. As for EF-NEMD simulations, the effect of a transmembrane pressure difference can be mimicked by applying a constant force in the x direction (Figure 4) on each small molecule [31,50]. Water molecules and hydronium ions transfer through the Nafion membrane under the driving force.…”
Section: Methodsmentioning
confidence: 99%
“…In an actual PEMFC system, a pressure difference is generated due to the different stoichiometric ratios of hydrogen and air. As for EF-NEMD simulations, the effect of a transmembrane pressure difference can be mimicked by applying a constant force in the x direction (Figure 4) on each small molecule [31,50]. Water molecules and hydronium ions transfer through the Nafion membrane under the driving force.…”
Section: Methodsmentioning
confidence: 99%
“…This method has been used in many previous studies to simulate nanoconfined flow. [56][57][58][59] The motion equation was integrated using the velocity Verlet algorithm with a time step of 1 fs. [60] The NEMD simulation was conducted for 10 ns to obtain a steady flow.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have found significant carbon isotope fractionation when monitoring the isotopic composition of released gas during canister degassing and transport simulation experiments. Further investigation revealed that the fractionation characteristics (duration and amplitude) during methane transport are correlated with the material composition, , pore structure, ,, GIP content, , and AGR, ,,,,, providing a novel approach to assess the gas-bearing parameters using isotopic fractionation. Li et al proposed a carbon isotope fractionation (CIF) model that can effectively characterize the entire shale gas degassing process based on experimental findings and mechanism analysis.…”
Section: Introductionmentioning
confidence: 99%